Looking like a state: Techniques of persistent failure in state capability for implementation - Lant Pritchett; Michael Woolcock; Matt Andrews (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
In many nations today the state has little capability to carry out even basic functions like security, policing, regulation or core service delivery. Enhancing this capability, especially in fragile states, is a long-term task. Countries like Haiti or Liberia will take many decades to reach even a moderate capability country like India, and millennia to reach the capability of Singapore. Short-term programmatic efforts to build administrative capability in these countries are thus unlikely to be able to demonstrate actual success, yet billions of dollars continue to be spent on such activities. What techniques enable states to 'buy time' to enable reforms to work, to mask non-accomplishment, or to actively resist or deflect the internal and external pressures for improvement? How do donor and recipient countries manage to engage in the logics of 'development' for so long and yet consistently acquire so little administrative capability? We document two such techniques: (a) systemic isomorphic mimicry, wherein the outward forms (appearances, structures) of functional states and organizations elsewhere are adopted to camouflage a persistent lack of function; and (b) premature load bearing, in which indigenous learning, the legitimacy of change and the support of key political constituencies are undercut by the routine placement of highly unrealistic expectations on fledging systems. We conclude with some suggestions for sabotaging these techniques.
Keywords: O2; H4; K4; L3; 330; organizations; capability; isomorphic mimicry; expectations